Constructing Gambling Reality: A Critical Multimodal Analysis on Online Gambling Advertisements - Mochammad Rizki Juanda; Eri Kurniawan; Budi Hermawan (Universitas Sebelas Maret, 2023)
This study aims to reveal the ideology contained in online gambling advertisements that appear on social media. The data for this qualitative descriptive research was three online gambling advertisements that were taken randomly on Instagram social media at the hashtag #judionline on September 18, 2022. The analysis process was carried out by analyzing the signs on the ads using a triangular semiotic theory framework by Charles S. Pierce. The findings showed that the three online gambling advertisements that appear on Instagram have similarities and differences in the use of the signs to construct the reality presented on online gambling advertisements. The continuity between the signs in online gambling advertisements creates an impression that online gambling is a fun, profitable and promising activity for the audience. The researcher suggests that readers who find online gambling advertisements on social media should be more careful and critical in reading the information raised by advertisements so that they can avoid things that can cause losses.